Victors and Vanquished : Spanish and nahua views of the conquest of Mexico - Schwartz, Stuart B. (Boston Bedford/St. Martin's, 2000)
In 1519 Hernán Cortés and a small band of Spanish conquistadors overthrew the mighty Mexican empire of the Aztecs. Using excerpts primarily drawn from Bernal Diaz's 1632 account of the Spanish victory and testimonies - many recently uncovered - of indigenous Nahua survivors, Victors and Vanquished clearly demonstrates how personal interests, class and ethnic biases, and political considerations influenced the interpretation of momentous events.
Includes bibliographies and index
Keywords: Tham Khảo